ANALISIS POTENSI AGROINDUSTRI KELAPA DI KABUPATEN PADANG PARIAMAN MENGGUNAKAN METODE DLQ (DYNAMIC LOCATION QUONTIENT) - Tiofani Setia Yusman; Fitriana Syahar (JURUSAN GEOGRAFI FIS UNP, 2021)
This study aims to: Know the superior products of coconut agro-industry in Padang Pariaman District in each sub-district; Knowing the potential of coconut agro-industry in Padang Pariaman Regency in the future. The method used in this research is quantitative with a descriptive approach which is useful in explaining all data and the results obtained from the calculation. The data used in this study is secondary data that has been compiled by the Integrated Services Investment Service and Industry. To see whether the coconut agro-industry in each sub-district in Padang Pariaman Regency becomes the base sector by calculating using the Location Quontient (LQ) analysis method. After obtaining the results of the calculation of LQ for each sub-district, the calculation using the Dynamic Location Quontient (DLQ) analysis method to see whether the coconut agro-industry in each sub-district in Padang Pariaman Regency will remain a sector basis or non-sector basis in the future. future sector basis or non-future basis. In this research, there are three types of agro-industry focus, namely copra, VCO and coconut cooking oil. In this study, from 17 sub-districts that exist, but not all districts that carry out coconut agro-industrial activities and VCO, cooking oil and copra agro- industry activities are dominated by the average yield of LQ and DLQ> 1 which means that it is very potential to be developed.